1985
DOI: 10.1021/j100266a041
|View full text |Cite
|
Sign up to set email alerts
|

A pulse radiolysis study of the leucocyanide of malachite green dye in organic solvents

Abstract: Microsecond pulse radiolysis studies have been carried out on the leucocyanide of malachite green dye (MGCN) dissolved in either 1,2-dichloroethane, chloroform, carbon tetrachloride, acetone, cyclohexane, benzene, toluene, dimethyl sulfoxide, AyV-dimethylformamide, methanol, 2-propanol, tetrahydrofuran, dioxane, benzonitrile, or acetonitrile. The transient absorption spectra obtained in argon-saturated solutions, and with various added electron scavengers (N20, 02, or CC14), indicate that there are several int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…III.͒ Two radiochromic systems that have been developed for radiographic imaging and dosimetry at absorbed doses greater than those used for radiation therapy are thin films containing either amino-triphenylmethane leucodyes or tetrazolium salts as the colorless radiation sensitive ingredients which are changed to deep colors upon irradiation. Historical details and the results of radiation chemical kinetics studies of these systems can be found in a series of publications by McLaughlin et al 2,[11][12][13]18,35,[42][43][44][45][46][47]…”
Section: Radiochromic Filmsmentioning
confidence: 99%
“…III.͒ Two radiochromic systems that have been developed for radiographic imaging and dosimetry at absorbed doses greater than those used for radiation therapy are thin films containing either amino-triphenylmethane leucodyes or tetrazolium salts as the colorless radiation sensitive ingredients which are changed to deep colors upon irradiation. Historical details and the results of radiation chemical kinetics studies of these systems can be found in a series of publications by McLaughlin et al 2,[11][12][13]18,35,[42][43][44][45][46][47]…”
Section: Radiochromic Filmsmentioning
confidence: 99%
“…Then the colored dye cation forms, absorbing at 600 to 640nm depending on the nature of the DTB. [14][15][16] An initial example of the color change of a prototype dosimeter formulated with a DTB and radical initiator in polyurethane is shown (Figure 2).…”
Section: Leuco Dyesmentioning
confidence: 99%
“…The initial radiolytic reaction is the dissociation of the radical initiator and subsequent reaction with LMG to create a radical which absorbs at ca 425 nm followed by the formation of the malachite green cation absorbing at 630 nm [ 51 52 ] ( Fig. 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…For the ortho - and para -methoxy derivatives, 7 and 8 , respectively, the interpretation of the steric and electronic contributions is not as straight forward since 8 is more dose sensitive than 7 and almost that of 5 . The addition of polar aprotic solvents such as DMSO also enhances the dose sensitivity [ 52 ].…”
Section: Reviewmentioning
confidence: 99%